A new alien polychaete species for the Mediterranean Sea: Glycera cinnamomea (Annelida: Glyceridae) - DAĞLI, Ertan; ÇINAR, Melih (Mediterranean Marine Science, 2022)
The present study reports the first occurrence of an alien glycerid polychaete worm, Glycera cinnamomea (Polychaeta: Glyceridae) in the Mediterranean Sea. Only one specimen of this species was collected on April 2021 on the shallow‒water sandy mud substratum (9m depth) in the western part of Mersin Bay, near Taşucu Turkey(in the Eastern Mediterranean Sea). This species is mainly characterized by having non–retractile branchiae with maximally five rami, emerging on the posterior side of the parapodia, and three types of proboscidial papillae. It is previously known from the Indo–Pacific areas and the Red Sea (Suez Bay). The species had been most probably introduced to the Mediterranean Sea via the Suez Canal (Lessepsian species) and have been unnoticed in the Levantine Sea so far. However, as the sampling area has one large international harbor (MersinHarbor), its introduction to the Mediterranean Sea via shipping cannot be ruled out. The morphological, ecological, and distributional features of this species are presented and discussed.